FOREST CRIMES AS A THREAT TO SUSTAINABLE FOREST MANAGEMENT - Özden, S.; Ayan, S. (Publishing House SB RAS, 2016)
From ancient times to the present day, forest public relations has been an issue on the agenda. This relationship’s purpose was initially needed for shelter and nutrition; however today this process has changed with urbanization, overpopulation and understanding the new functions of forests. When land ownership became a tool of production, offenses occurred in order to convert forestlands to agricultural lands. So the vast majority of the world’s forests have been lost for this reason. Today, deforestation is occurring in tropical countries that are expecting to gain agricultural area. The purpose of this study is to investigate the relationship between urbanization and the qualitative and quantitative characteristics of forest crimes, which are a major obstacle for sustainable forestry. Although forests cover about 27 % of Turkey’s territory, the forests are losing viability; the status of wood raw material per unit area and the total area of the country in the ratio of productive forests are becoming critical in Turkey. Turkey’s rugged terrain and factors such as human interventions, fires, deforestation for agriculture, illegal cuttings, or improper grazing reduce existing forests or cause deterioration of their structure. In the past, deforestation, as a result of human interventions in Turkey, was done by forest villagers who live in rural areas. The forest crimes depend on various socio-economic reasons and have many adverse effects on the sustainability of forest and forest existence. In developed countries, illegal interventions such as opening, grazing, cutting, occupation, use, settlement, or hunting crimes have been largely eliminated because of the absence of cadastral problems, the existence of more responsive people to protect the environment and forests and a rural population, which has a higher standard of living. In the last 20 years, there has been both a dramatic decrease in the population living in rural areas and a decrease of forest crimes in rural areas. On the other hand, legal and illegal forest attacks have been increasing due to urbanization in this process. This study was conducted to evaluate Yeşilirmak river basin forest crimes of the last 11 years. Yeşilirmak river basin occupies 3 964 375 ha, which is approximately 5 % of Turkey’s total area and 519 km in length.
Keywords: Turkey; forest offences; urbanization; Forestry; SD1-669.5; forest-public relations; rural development; 2. Zero hunger; 1. No poverty; 15. Life on land; 16. Peace & justice; 6. Clean water; 12. Responsible consumption; 13. Climate action; 11. Sustainability